Apply the distributive property.

Apply the distributive property.

Apply the distributive property.

Combine the opposite terms in <math><mstyle displaystyle="true"><mn>3</mn><mi>x</mi><mrow><mo>(</mo><mn>3</mn><mi>x</mi><mo>)</mo></mrow><mo>+</mo><mn>3</mn><mi>x</mi><mo>⋅</mo><mn>2</mn><mo>-</mo><mn>2</mn><mrow><mo>(</mo><mn>3</mn><mi>x</mi><mo>)</mo></mrow><mo>-</mo><mn>2</mn><mo>⋅</mo><mn>2</mn></mstyle></math> .

Reorder the factors in the terms <math><mstyle displaystyle="true"><mn>3</mn><mi>x</mi><mo>⋅</mo><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn><mrow><mo>(</mo><mn>3</mn><mi>x</mi><mo>)</mo></mrow></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>2</mn><mo>⋅</mo><mn>3</mn><mi>x</mi></mstyle></math> from <math><mstyle displaystyle="true"><mn>2</mn><mo>⋅</mo><mn>3</mn><mi>x</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>3</mn><mi>x</mi><mrow><mo>(</mo><mn>3</mn><mi>x</mi><mo>)</mo></mrow></mstyle></math> and <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Simplify each term.

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Do you know how to Simplify (3x-2)(3x+2)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.